2012
DOI: 10.3892/ol.2012.598
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase and thymidine phosphorylase mRNA expression in primary lesions using laser capture microdissection is useful for prediction of the efficacy of FOLFOX treatment in colorectal cancer patients with liver metastasis

Abstract: Abstract. Chemotherapy with FOLFOX, which is a combination of 5-fluorouracil (5-FU)/leucovorin (LV) and oxaliplatin, has been used worldwide for the treatment of metastatic colorectal cancer patients. The aim of this study was to examine the candidates for predictors of the efficacy of the FOLFOX treatment regimen in colorectal cancer patients with liver metastasis, using formalin-fixed paraffin-embedded specimens. We investigated the mRNA levels of thymidylate synthase (TS), thymidine phosphorylase (TP), dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…A positive correlation between TS and TP mRNA expression has also been reported by van Triest et al [30]. Therefore, the results of our study are considered to be reliable and consistent with those reported in previous studies [17,31]. Although many previous studies have investigated the expression of 5-FU metabolic enzymes to assess whether they are predictive biomarkers of 5-FU response, the impact of these enzymes as biomarkers is still weak.…”
Section: Discussionsupporting
confidence: 93%
“…A positive correlation between TS and TP mRNA expression has also been reported by van Triest et al [30]. Therefore, the results of our study are considered to be reliable and consistent with those reported in previous studies [17,31]. Although many previous studies have investigated the expression of 5-FU metabolic enzymes to assess whether they are predictive biomarkers of 5-FU response, the impact of these enzymes as biomarkers is still weak.…”
Section: Discussionsupporting
confidence: 93%
“…Treatment with FOLFIRI was also administered as second-line chemotherapy to ~70% of patients receiving mFOLFOX6 treatment, and hence, the patients with increased survival rates were exposed to 5-FU for a long time. Numerous studies have indicated that MCRC patients with lower TS expression have a favorable outcome following 5-FU-based chemotherapy compared with patients with high TS expression (10,28). A previous study revealed that TS mRNA expression in rectal cancer patients with the TS -3′-UTR −6/−6 and −6/+6 genotypes was significantly lower compared with patients with the TS -3′-UTR +6/+6 genotype, resulting in a favorable outcome following neoadjuvant 5-FU-based chemoradiation (29).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis, associated with the metabolism of 5-FU and oxaliplatin, has been intensively studied (69). It has been reported that thymidylate synthase ( TS) and thymidine phosphorylase ( TP ) mRNA expression levels are useful markers for predicting the efficacy of FOLFOX treatment in CRC patients with liver metastasis (10). In addition, advances in molecular biology indicate that a number of drug metabolism genes have polymorphisms that alter levels of expression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, after the implantation, released 5-FU plays relevant functions after diffusing into extracellular tissue fluid; the extremely small amount of the drug entering into the blood through the capillary wall results in low peak concentration, which avoids toxic and side effects. [10][11][12][13] We found that sustained-release 5-FU could inhibit liver cancer and rapid proliferation of residual cancer cells after surgical resection, and sustained-release 5-FU conforming to the concept and requirement of regional chemotherapy and interstitial chemotherapy was operable and valuable.…”
Section: Discussionmentioning
confidence: 99%